Foreign Direct Investment and the Environment: Disentangling the Impact of Greenfield Investment and Merger and Acquisition Sales - Ashraf, Ayesha (Archīum Ateneo, 2020)
Purpose This study aims to examine the effect of greenfield foreign direct investment (GFDI) and mergers and acquisitions (M&A) on the environment and more specifically, on the sectoral emissions of CO2. The authors identify significant differential and income effects with various data classifications of foreign direct investment (FDI) mode of entry. Design/methodology/approach The authors use system generalized method of moments with instruments for income and GFDI and M&A, which allows us to control for present reverse causality and endogeneity of income and the two modes of FDI. Findings Evidence from the full sample reveals that GFDI increases pollution, supporting the pollution haven hypothesis, while M&As decrease pollution in line with the halo effect hypothesis. GFDI flowing into poorer countries worsens the environment, while M&As flowing to industrialized economies reduce pollution. Entry-mode effects are also present at the level of industry emissions. GFDI in developed economies decreases pollution in transport industry but increases it in poorer countries. Practical implications The authors demonstrate: first, a recipient country level-of-development effect: GFDI investment flowing into poorer countries has harmful effects on environment, but no significant effect in rich economies, while M&As flowing to industrialized economies have a beneficial effect to the environment, supporting the halo hypothesis. Second, the authors demonstrate a differential entry-mode effect at the industry level: GFDI in developed economies decreases pollution from transport industry, while both modes of entry in developing economies increase it. Social implications M&As emerge as a type of FDI that is less harmful to the environment. This is especially true in the case of developed economies. However, policymakers should oversee strictly the inbound GFDI flows and determine whether they carry “dirty” or “clean” production processes. This is the type of FDI to be regulated and scrutinized to ensure that economic development is fostered alongside environmental conservation. Originality/value In existing theoretical and empirical literature, little guidance is available on which mode of entry would have greater effect on the environment of the host country. This paper answers this issue by disaggregating FDI flows into GFDI and M&As and examining how each mode of entry impacts pollution in host countries. To the best of the knowledge, this is the first study that analyzes the environmental impact of the two modes of entry of FDI while disentangling the environmental Kuznets curve effect from the halo effect.